Molecular cloning and in silicon characterization of full-length Xet and Cesa cDNA in Shorea parvifolia Dyer ssp. Parvifolia - Lau, Ee Tiing (Universiti Malaysia Sarawak (UNIMAS), 2008)
Isolation of high integrity RNA is difficult in a variety of plants because of the presence of secondary metabolites that normally interfere with RNA isolation procedures and other downstream applications. In the present study, an improved method of total RNA isolation from young leaves and developing xylem tissues of Shorea parvifolia Dyer ssp. parvifolia rich in secondary metabolites was established. The described method is ion detergent CTAB (cetyltrimethylammonium bromide)- based extraction and combined with CTAB/butanol purification method. By using this improved protocol, total RNA in better quality and quantity than several conventional established isolation methods was obtained. The RNA yields ranged from 97-127µg of total RNA per gram of tissues used. The isolated RNA was suitable for reverse transcriptions and rapid amplification of cDNA ends-polymerase chain reaction (RACE-PCR) analysis. Two master genes were studied in detail in the present study, i. e. cellulose synthase (CesA), a key enzyme involved in biosynthesis of cellulose (the primary structural component of the plant cell walls), and the xyloglucan endotransglycosylase (XET), a key enzyme required for plant cell wall reconstruction. In this study, the full-length of xyloglucan endotransglycosylase (SpXETI) and cellulose synthase (SpCesAl) cDNA from an economically important tropical tree species, S. parvifolia ssp. parvifolia was successfully isolated. The full-length SpXETI cDNA was 1162bp long with an 879bp open reading frame encoding a 293 amino acid protein. The predicted SpXET 1 peptide contained the conserved domain of DEIDFEFLG, a putative N-glycosylation site, ADDWATRGGLEKTDW motif and 4 conserved cysteine residues. Amino acid sequence obtained was highly identical (87%) among the SpXETI and PttXET16A (GenBank accession number AAN87142) from Populus tremula x Populus tremuloides hybrid. This result clustered the SpXET1 into subfamily I of the XET members and revealed the involvement of SpXETI in transglycosylation reaction between xyloglucan chains in the secondary vascular tissues of S. parvifolia ssp. parvifolia. Characterization of full-length SpCesAl cDNA showed that the total length of this cDNA was 3308bp long with open reading frames of 3120bp long encoding a 1040 amino acid protein. The predicted SpCesAl peptide contained N-terminal cysteine rich zinc binding domain that corresponds to cell microfibril structures, seven putative transmembrane helices (TMH), four U-motifs that contain a processive glycosyltransferases signature D, D, D, QxxRW motif, an alternating conserved region (CR-P) and 2 hypervariable regions (HVR). The entire shared domain structures suggest the functional role of SpCesAI is involved in cellulose biosynthesis in secondary vascular tissues of S. parvifolia ssp. parvifolia. Sequence comparison also revealed the high similarity (87%) among the SpCesA 1 and PtrCesA2 (GenBank accession number AAM26299), the functional protein of Populus tremuloides secondary cell wall biosynthesis. This further implies the involvement of SpCesA 1 in catalyzing the cellulose biosynthesis of secondary cell wall rather than primary cell wall. Thus, this information will be useful in providing a better understanding of the mechanism of cell wall biosynthesis and reconstruction, and during wood formation in tropical hardwood species. Besides, these full-length cDNAs can be used for developing genetic markers to identify economic trait loci (ETL) for wood quality traits. By associating genotypes with phenotypes, early selection of high quality planting materials could be achieved at the seedling stage.